BUSINESS STRATEGIC ANALYSIS LEMBAGA KEUANGAN MIKRO BERBASIS BUMDES (LKM-BUMDES) DALAM PENGUATAN EKONOMI DESA - Muhammad Feriady (Equilibria Pendidikan : Jurnal Ilmiah Pendidikan Ekonomi, 2018)
This study aims to analyze business strategies owned by Micro Finance Institutions BUMDES Samirono in an effort to develop business and impact on community empowerment. This research was conducted in Gogik Village, West Ungaran District, Semarang Regency. The method used in this research is quantitative descriptive method with IFE and EFE environment analysis and SWOT Analysis. The results of this study showed that in the analysis of Internal and External Factors found by the researchers that internal factors are on average condition with IFE scores of 2.539. In the analysis of external factors have an EFE score of 2.662 which means the position of the organization in a state of being. The SWOT analysis shows that the alternative strategy that needs to be developed by the Samirono BUMDES Micro Finance Institution (LKM-BUMDES) is by maintaining a family organization that is familial in order to address the challenges and threats of the organization. The conclusion that can be obtained from this research is Village Finance Institution has its own characteristic in doing business activity. The aspect of familial, flexible and customizing the characteristics of the village community is the key to the success of the Samirono Micro Finance Institution (LKM-BUMDES) in running the savings and loan business and improving the welfare of the surrounding community.